Passing patterns before and after goal scoring in FA Premier League Soccer - Redwood-Brown, A. (International Journal of Performance Analysis in Sport, 2008)
Previous investigations of scoreline effects in soccer have looked at all periods of matches where a team is winning, losing or drawing. The current investigation focussed instead on the 5 minutes leading up a goal being scored and the 5 minutes that followed the goal. The frequency of passing and the percentage of successful passes were compared between these periods and the average for 5 minutes within the half of the match in which the goal was scored. There were 285 goals from 120 English FA Premier League matches that were analysed. In the 5 minutes that preceded a goal, the scoring team played a significantly greater percentage passes accurately than the average for the half (p < 0.017), while the conceding team played significantly fewer passes (p < 0.017). After the goal was scored, the scoring team played significantly fewer passes (p < 0.017) and a lower percentage of passes were played accurately (p < 0.017) than the average for the half of the match where the goal was scored. Accurate passing not only retains possession but may also lead to scoring opportunities while also restricting opposition possessions and scoring opportunities.